Anesthetic management of epilepsy surgery in a patient previously diagnosed with Takotsubo cardiomyopathy: A case report. Issue 42 (21st October 2022) - Xu, Yue; Li, Yi; He, Jinhua; Li, Jianli; Liu, Meinv; Zhang, Huanhuan
Abstract : Rationale: Takotsubo cardiomyopathy (TC), also known as stress cardiomyopathy, apical ballooning syndrome, octopus pot cardiomyopathy and broken heart syndrome, is characterized by wall motion abnormalities of the left ventricle. Patient concerns: Here, we reported a 73-year-old woman diagnosed with TC induced by epilepsy before 3 months presented to the authors' hospital with generalized tonic-clonic seizure. She was scheduled for intracranial tumor resection to cure the epilepsy. Diagnosis: She was diagnosed with epilepsy and TC. Interventions: Anesthesia management plays an important role in patients with a past history of TC. Outcomes: At the 1-week follow-up, she had fully recovered without obvious abnormalities. Lessons subsections: We emphasize the importance of individualized anesthesia management in patients with a past history of TC.